2012
DOI: 10.1002/chem.201201041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticoagulant Activity of Bioisosteric Sulfonic‐Acid Analogues of the Antithrombin‐Binding Pentasaccharide Domain of Heparin

Abstract: Two pentasaccharide sulfonic acids that were related to the antithrombin-binding domain of heparin were prepared, in which two or three primary sulfate esters were replaced by sodium-sulfonatomethyl moieties. The sulfonic-acid groups were formed on a monosaccharide level and the obtained carbohydrate sulfonic-acid esters were found to be excellent donors and acceptors in the glycosylation reactions. Throughout the synthesis, the hydroxy groups to be methylated were masked in the form of acetates and the hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 49 publications
0
39
0
1
Order By: Relevance
“…A wide variety of glycosyl donors (6,7,8) and promoters were tested in the glycosylation of units D and E. Formation of an aglycon transfer side product (33a,b) was observed when glycosyl bromide (30) and b-thioglycoside (29) were used as the donors (Scheme 7.). This competitive side reaction could be avoided with the use of a-thioglycoside at a low temperature and a short reaction time.…”
Section: Hivatkozásokmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of glycosyl donors (6,7,8) and promoters were tested in the glycosylation of units D and E. Formation of an aglycon transfer side product (33a,b) was observed when glycosyl bromide (30) and b-thioglycoside (29) were used as the donors (Scheme 7.). This competitive side reaction could be avoided with the use of a-thioglycoside at a low temperature and a short reaction time.…”
Section: Hivatkozásokmentioning
confidence: 99%
“…A diszulfonsav származék (4) hatékonyabb volt a referencia vegyületeknél (2, 3), a pentaszacharid-triszulfonsav (5) viszont lényegesen kisebb aktivitást mutatott (1. ábra). 7 Látva, hogy a lecserélni kívánt szulfát-észter csoportok helyzete és száma meghatározó a vegyületek aktivitását illetõen, elhatároztuk újabb izoszter szulfonsav származékok szintézisét, és antikoaguláns hatásának vizsgálatát. Doktoranduszi kutatásom keretében feladatom volt az idraparinux primer helyzetû szulfátészter csoportjainak szisztematikus cseréjével a 6-10 mono-és diszulfonsavak szintézise (2. ábra).…”
unclassified
“…Similarly, substitution of the ring oxygen with carbon shows increased stability and lower clearance in vivo [42]. The substitution of an oxygen for a carbon can also be used to stabilized labile groups such as sulfate [43] and phosphate [44,45] on sugar hydroxyls. In the phosphate case, the more stable phosphonate can be used specifically as an enzyme inhibitor [45] or can be be further substituted at the alpha-position for covalent inhibition [44].…”
Section: Non-natural Sugars To Enhance Glycoside Stabilitymentioning
confidence: 99%
“…Such automated synthetic methods to string together or site-specifically incorporate sugars containing conformationally-locked sugar mimetics are also needed. The ability to freeze one of the ring conformations of a pyranoside could result in mimics with increased affinity and specificity for their targets as shown with the importance of L-IdoA in heparan sulphate in targeting the blood-coagulation factor Xa [43]. The work to design and synthesize more complex non-natural sugars has only just begun.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Recently, we found that isosteric sulfonic acid analogues of the antithrombin‐binding domain of heparin in which two or three primary sulfate esters were replaced with a sodium sulfonatomethyl group inhibited the blood coagulation proteinase factor Xa; however, this occurred at different rates depending on the position of the sulfonatomethyl moiety 5b. To gain deeper insight into the structure–activity relationship of the anticoagulant action of the sulfonic acid derivatives, we decided to prepare heparinoid pentasaccharides by systematic replacement of the sulfate esters with a sodium sulfonatomethyl moiety.…”
Section: Introductionmentioning
confidence: 99%